TASK-BASED LEARNING AND ITS EFFECT ON VOCABULARY ACQUISITION IN ESL LEARNERS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study explains how Task-Based Learning (TBL) helps ESL learners improve their vocabulary. Many students find it difficult to remember new words when they only study word lists. TBL gives learners real tasks where they must use new vocabulary to communicate. In this study, one group learned vocabulary through TBL activities, and another group learned with traditional exercises. After eight weeks, the TBL group learned more words and remembered them better. They also said that learning with tasks was more interesting and made them more confident. The results show that TBL is a useful way to help students learn and use new vocabulary.